Pengaruh Media Flash Card terhadap Pemahaman Siswa Pada Materi Hak dan Kewajiban Kelas III SD Negeri 1 Sungailiat - Amanda Sri Febianti; Sasih Karnita Arafatun; Eka Wahyuningsih (JBES (Journal Basic Education Skills), 2024)
The lack of use of a variety of learning media during the learning process, which is teacher-centered, impacts some students' lack of understanding in the learning process and is the driving force behind this research. This research aims to determine the effect of flashcard media on students' understanding of the material on rights and obligations for class III SD Negeri 1 Sungailiat. This research uses a quantitative approach with the quasi-experimental design method and a nonequivalent control group design. The sample collection technique uses a saturated sampling technique, where the entire population will be sampled. The sample in this study consisted of 26 students from class III A, the experimental class, and 26 students from class III B, the control class. The data collection technique was conducted by giving a five-question essay test. The data analysis techniques in this research are normality testing using the Kolmogorov-Smirnov test, homogeneity testing using the Levene test, and hypothesis testing using the Independent Sample t-test. The research results show that the average score obtained for the experimental class was 80.769, which was higher than the control class, namely 70.962. Using an independent sample t-test, the results show that t-table = 2.009 < t-count = 3.141. This means that Ha is accepted and Ho is rejected. This means that flashcards affect how well class III students at SD Negeri 1 Sungailiat understand the material on rights and obligations.